Kemampuan Menggunakan Konjungsi Antarkalimat pada Paragraf Argumentatif Dengan Tema "Kerusakan Lingkungan" oleh Siswa Kelas X SMA Negeri 5 Kota Padangsidimpuan - Riskiana Aritonang, Devinna (Jurnal Hata Poda, 2023)
This study aims to determine whether there is an ability to use inter-sentence conjunctions in argumentative paragraphs with the theme "Environmental Damage" by class X students of SMA Negeri 5 Padangsidimpuan City with the research population being all class X SMA Negeri 5 Padangsidimpuan City, totaling 218 students, and the sample are 32 students in total. To obtain data in the research, the authors submit tests to students, cloze tests on the ability to use conjunctions between sentences (variable X) and essay tests on argumentative paragraphs with the theme "Environmental Damage" (variable Y). The research method uses descriptive quantitative analysis and statistical analysis using the correlation formula "r" product moment. Then the highest score obtained for each variable is 90 and the lowest 70 with an average of 75.9 for the X variable, and the highest 80 and 70 the lowest with an average of 75.6 for the Y variable. In the data that has been submitted it is obtained rxy= equal to 0.448 this means rxy rtable significant level of 5% or 1%, namely 0.448 0.361. Thus the hypothesis proposed can be accepted for truth.Keywords: Conjunctions BetweenSentences, Argumentative Paragraphs.